The Periodic Table. The Power of Systematization. The Importance of Precision - Mó, Otilia; Yáñez, Manuel (Academia das Ciências de Lisboa, 2022)
One hundred and fifty years ago the first important systematization in the realm of chemistry was done, ordering the elements in terms of its atomic mass. This first attempt was crucial even though not totally correct. A better knowledge of the atomic structure improved this initial systematization in terms of the atomic number; but a real understanding of the periodicity in the atomic properties was possible only when the mathematical functions describing the electrons within an atom were obtained. The use of the variational principle looking for the minimal energy of an atomic or molecular system was the engine behind this understanding, though soon it became also clear that, in some specific cases, second order properties could be not adequately described even if the precision got for the energy was large. Magnetic properties are a good example, or the singularity of the elements of the first row of the periodic table with respect to the others within the same group. Some of these questions will be analyzed in our presentation.
Keywords: Tabela periódica